Comparing the adsorption of selected pharmaceuticals onto a peat-based and a coal-based activated carbons in a fixed-bed column - Aaltonen, Johanna (2024)
Activated carbon filtration is a common way to eliminate pharmaceuticals and other micropollutants from water. Still, the process at both wastewater and drinking water treatment plants is unsuccessful in eliminating pharmaceuticals completely which is why they end up in the nature and in our drinking water. The aim of this study was to investigate the adsorption of select pharmaceuticals onto two different activated carbons (ACs): a peat-based AC under research and development (R&D) and a commercial coal-based carbon called Filtrasorb TL830. 15 pharmaceuticals were selected to the study of which 10 were antibiotics and five were antiretroviral drugs (ARVDs). Preliminary testing was done with different concentrations of methylene blue. The pharmaceuticals were dissolved in ultrapure MilliQ (MQ) water and run through an activated carbon bed with a bed height of 1,5 cm and a flow rate of 10 ml/min in a fixed-bed column. The samples were analyzed with HPLC-MS/MS. The adsorbed mass of pharmaceuticals per a gram of AC varied between 0,95-1,49 mg/g with R&D peat and between 0,68-1,64 mg/g with Filtrasorb. The study failed to determine maximum adsorption capacity as the runtime of the study was too short. With R&D peat, the best adsorbed pharmaceutical was rifampicin and the worst adsorbed was zidovudine with the removal efficiency varying between 55 and 87%. With Filtrasorb, the adsorption efficiency varied between 40 and 96% and the best adsorbed was valacyclovir and the worst erythromycin. Although the variation was bigger with Filtrasorb, and R&D peat was able to adsorb slightly more pharmaceuticals altogether, there was no significant difference between the ACs. The difference between the removal efficiencies was most likely due to competitive adsorption, as no common trend was found in the physiochemical properties of the pharmaceuticals or ACs. The results of this study showed that both ACs can remove pharmaceuticals from water equally well, although further studies are still needed with longer runtimes to determine maximum adsorption capacities.